Case Report: Novel mutations in TBC1D24 are associated with autosomal dominant tonic-clonic and myoclonic epilepsy and recessive Parkinsonism, psychosis, and intellectual disability - Banuelos, Erika (F1000Res, 2017)
Mutations disrupting presynaptic protein TBC1D24 are associated with a variable neurological phenotype, including DOORS syndrome, myoclonic epilepsy, early-infantile epileptic encephalopathy, and non-syndromic hearing loss. In this report, we describe a family segregating autosomal dominant epilepsy, and a 37-year-old Caucasian female with a severe neurological phenotype including epilepsy, Parkinsonism, psychosis, visual and auditory hallucinations, gait ataxia and intellectual disability. Whole exome sequencing revealed two missense mutations in the TBC1D24 gene segregating within this family (c.1078C>T; p.Arg360Cys and c.404C>T; p.Pro135Leu). The female proband who presents with a severe neurological phenotype carries both of these mutations in a compound heterozygous state. The p.Pro135Leu variant, however, is present in the proband’s mother and sibling as well, and is consistent with an autosomal dominant pattern linked to tonic-clonic and myoclonic epilepsy. In conclusion, we describe a single family in which TBC1D24 mutations cause expanded dominant and recessive phenotypes. In addition, we discuss and highlight that some variants in TBC1D24 might cause a dominant susceptibility to epilepsy